Performance assessment of wind farms - Vaz, Clara B. (2014)
This study develops a methodology to provide insights regarding the performance of wind farms from a European player in energy sector. Firstly, the DEA is used to measure the performance of wind farms in generating electricity from the resources available and nondiscretionary variables such as wind (speed and availability). This analysis enables to identify the benchmarks whose best practices can be emulated by inefficient units and provides useful information for regulators in the sector. Secondly, bootstrap procedures are applied to obtain statistical inference on the efficiency estimates.